(untitled) (Contemporary Mathematics, 2025)
Water pollution remains a critical concern for Malaysian rivers, particularly due to increasing urbanization, industrial activities, and climate change. These factors have significantly degraded river quality through erosion, sedimentation, and pollution, disrupting the traditional relationship between communities and rivers. The Terengganu River, for instance, has experienced a marked decline in water quality, largely attributed to irresponsible human practices such as improper waste disposal. Previous research underscores the need for enhancing public ecological awareness. This study aims to develop a Public Perception Index (PPI) to assess and enhance community awareness of river pollution, especially among populations residing near rivers. Using the Fuzzy Delphi Method (FDM), 25 expert participants evaluated and validated key assessment criteria. From an initial set of eleven factors, eight were retained based on consensus analysis. The FDM results identified government roles as the most influential factor, while urbanization ranked lowest in importance. These weighted factors were incorporated into a composite index, leading to the formulation of a general mathematical model for the PPI. The study presents a novel approach to quantify public perception and promote environmental awareness, contributing to sustainable river management efforts in Malaysia.